Simulation of the effect of polarization Coulomb field scattering on device linearity in AlGaN/GaN heterostructure field effect transistors using the Monte Carlo method - Yongxiong Yang; Zhaojun Lin; Mingyan Wang; Heng Zhou; Yang Liu; Guangyuan Jiang (AIP Advances, 2021)
This paper demonstrates the improvement of device linearity in AlGaN/GaN heterostructure field effect transistors (HFETs) using polarization Coulomb field (PCF) scattering and investigates the relationship between device linearity and PCF scattering under 10 and 20 V drain bias. The mobility of the gate-to-source region in AlGaN/GaN HFETs is calculated using the Monte Carlo method. We find that PCF scattering decreases with an increase in gate bias (from −3 to −0.5 V) under high field conditions, leading to lower gate-to-source resistance. Under 20 V drain bias, linearity is worse than under 10 V drain bias. The transconductance drop is significant in AlGaN/GaN HFETs, which damages linearity. By adopting an appropriate drain bias, PCF scattering can alleviate transconductance drop and improve the linearity of AlGaN/GaN HFETs.